Harvest and utilization of chemical energy in wastes by microbial fuel cells. (3rd March 2016) - Sun, Min; Zhai, Lin-Feng; Li, Wen-Wei; Yu, Han-Qing
Abstract : Energy generated from wastes by using MFC technology could be effectively stored and utilized for real-world applications. Abstract : Organic wastes are now increasingly viewed as a resource of energy that can be harvested by suitable biotechnologies. One promising technology is microbial fuel cells (MFC), which can generate electricity from the degradation of organic pollutants. While the environmental benefits of MFC in waste treatment have been recognized, their potential as an energy producer is not fully understood. Although progresses in material and engineering have greatly improved the power output from MFC, how to efficiently utilize the MFC's energy in real-world scenario remains a challenge. In this review, fundamental understandings on the energy-generating capacity of MFC from real waste treatment are provided and the challenges and opportunities are discussed. The limiting factors restricting the energy output and impairing the long-term reliability of MFC are also analyzed. Several energy storage and in situ utilization strategies for the management of MFC's energy are proposed, and future research needs for real-world application of this approach are explored.